A New Topology of Embedded Z-H Buck-Boost Converter - E. Babaei; H. Feyzi; R. Gholizadeh-Roshanagh (AUT Journal of Electrical Engineering)
In this paper, a new embedded Z-H (EZ-H) buck-boost converter is proposed. In this topology, two identical dc voltage sources are embedded in a LC network in a series connection with the inductors. The proposed converter eliminates the shoot-through (ST) switching state and there is no need for a front-end diode. Other advantages of the proposed topology are having capability of buck and boost operations in one structure; reaching the maximum gain in the duty cycle near 0.5; lowering ripples of voltage and current; and particularly reducing the voltage stress on the capacitors. In this paper, the voltage and current equations of all the components are extracted with considering all the operation modes. In addition, a suitable switching method is presented for the proposed converter to generate the desired output voltage. The ripple values of inductors and capacitors are calculated. Simulation results by the PSCAD/EMTDC software show accuracy and performance of the proposed.converter.